When God alters our fate: Relational freedom in Romans 5:1-11 and 8:18-39 - Joubert, Stephan (Stellenbosch Theological Journal, 2018)
Fate played an enormous role in the Ancient Mediterranean world. Fate was personified in numerous ancient deities such as the Keres, the Moirae, and Fortuna. At the same time Stoic views on fate, as a chain of causes, impacted hugely on the ancient' general view on fate as an inexorable force which cannot be opposed, or whose direction and eventual outcomes cannot be changed. Against the backdrop, Paul's understanding of the nature of God's presence, actions and influence in the lives of believers in Romans 5:1-10 and 8:18-39 is discussed. Fate, in the sense of that which has been predetermined and written into the lives of individuals before birth, and which comes into existence in many different, fixed forms, or fate as a chain of causes, is never on Paul's mind. God's foreordained plan is not a predetermined, unalterable fate for each and every person over which they have no control or say whatsoever. Rather, God's πρόθεσις (prothesis) relates to the salvation of all believers. God refuses to surrender his people to their fate, namely death and eternal destruction. He changes fate into destiny for all who believe in Christ.